Valproate and Carbamazepine Comparative Trial - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1995)
The efficacy and side-effects of sodium valproate (VA) and carbamazepine (CBZ) were compared in 260 children (5 to 16 years of age) with primary generalized epilepsy or partial epilepsy followed for three years at 63 outpatient clinics in the UK and Ireland and results were reported from Addenbrooke's Hospital, Cambridge, the Hospital for Sick Children, Great Ormond Street, London, and the Trial Office at Sanofi Winthrop Ltd, Guildford, Surrey, UK.